INTEGRATING TRADITIONAL CRAFT PRACTICES INTO FASHION EDUCATION: A PATHWAY FOR SUSTAINABLE RURAL DEVELOPMENT - Thakur, Manasi Nachiket; Atre, Avadhut (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India has a rich tradtion of arts and crafts with immense diversitiy in its forms. However, the future generations do not find it lucrative enough to persue it further due to access to contemporary markets and lack of formal education. Fashion design education thrives on how one integrates the arts and crafts into the formal ways of learning. The research explores positioning of fashion education—not merely as aesthetic or cultural inputs for design innovation, but as independent and employable skill sets that can groom a new generation of skilled craftspeoplecraft. It goes beyond preserving motifs and techniques—it lies in creating equitable partnerships, entrepreneurial opportunities, and consistent livelihood avenues for artisans. It can be achieved by including traditional craft practices, market understanding, business acumen into vocational fashion curriculum. The research involves various initiatives by designers, entreprenuers, brands, educational institutions explained by way of case studies & interviews. The inclusive and appropriate education will prepare the designers to be socially responsible change makers who can enable rural artisans to thrive in today’s competitive market while honoring their cultural legacy.